MISTISISME JALAL AL-DIN AL-RUMI DALAM PERSPEKTIF ANNEMARIE SCHIMMEL - Mubaidi Sulaeman (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2020)
Most of Orientalis misunderstood about Islam like they were made to touch an elephant, each described it according to the part of body his hands had touched: to one the elephant appeared like a throne, to another like a fan, or like water pipe, or like a pillar. Schimmel attempt to understands of Islam (sufism) very well used Phenomenology Approach, and the result is amazed the others orientalist and most of moeslem. Schimmel said The plurality of signs is necessary to veil the eternal One who is transcendent and yet ‘closer than the neck vein’ (QS 50:16). The signs show the way into His presence, where the believer may finally leave the images behind. Ru>mi one of Sufis who completed that understading passed way divine love.